2023
DOI: 10.1111/iju.15208
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the past and present to change the future: Endoscopic management of upper urinary tract urothelial carcinoma

Abstract: Current guidelines recommend endoscopic management (EM) for patients with low‐risk upper urinary tract urothelial carcinoma, as well as those with an imperative indication. However, regardless of the tumor risk, radical nephroureterectomy is still mainly performed worldwide despite the benefits of EM, such as renal function maintenance, no hemodialysis requirement, and treatment cost reduction. This might be explained by the association of EM with a high risk of local recurrence and progression. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Although a higher rate of upper urinary tract recurrence is a drawback of EM and rigorous surveillance or repeated intervention may be necessary, the crucial information is that EM and nephroureterectomy have similar oncological outcomes in terms of cancer-specific survival and overall survival, especially cases with low-risk tumors. 1 A nephronsparing approach with good cancer control would lead to overall patient benefits, considering the longer life expectancy with better renal function. 5 Yusuke Goto MD, PhD Department of Urology, Chiba University Graduate School of Medicine, Chiba, Japan yusukegoto@chiba-u.jp DOI: 10.1111/iju.15223…”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a higher rate of upper urinary tract recurrence is a drawback of EM and rigorous surveillance or repeated intervention may be necessary, the crucial information is that EM and nephroureterectomy have similar oncological outcomes in terms of cancer-specific survival and overall survival, especially cases with low-risk tumors. 1 A nephronsparing approach with good cancer control would lead to overall patient benefits, considering the longer life expectancy with better renal function. 5 Yusuke Goto MD, PhD Department of Urology, Chiba University Graduate School of Medicine, Chiba, Japan yusukegoto@chiba-u.jp DOI: 10.1111/iju.15223…”
Section: Editorial Commentmentioning
confidence: 99%
“…Yoshida et al. reviewed recent studies regarding endoscopic management (EM) of UTUC, 1 focusing mainly on current clinical issues including diagnostic procedures, surgical procedures, and follow‐up after surgery. They found that accurate patient selection, surgical procedures, and perioperative management are vital for improving the oncological outcomes of EM.…”
mentioning
confidence: 99%
“…Indeed, there is very little evidence available or even data related to cytoreductive surgery for mUTUC. A recent study by Yoshida et al suggested cytoreductive surgery outcomes improve when supplemented with chemotherapy although this was only preliminary research that requires further investigation ( 9 ).…”
Section: Introductionmentioning
confidence: 99%